A Rare Presentation of A Giant Epidermal Cyst of The Parietooccipital Region: A Case Reports - Kereh, David; Septiman, Septiman (The New Ropanasuri Journal of Surgery, 2019)
Introduction. Epidermal cysts are common benign cutaneous cysts. An epidermal cyst may be classified as a giant epidermal cyst if it exceeds 5 cm. Giant epidermal cysts with a diameter of 5 cm or more are rare but have been reported. The epidermal cyst rarely discloses malignancy. Although rare, a case of malignant change of benign epidermal cyst is possible. We describe here a rare case of a giant epidermal cyst of the parietooccipital region in a 35-year-old man. Case Illustration. A 35-year-old man was admitted to the hospital with a huge swelling over the scalp for the past 30 years. The swelling was non-tender, cystic, measuring 18x13x 9 cm, and was situated in the parietooccipital region. Skull CT revealed an oval shape, hypodense mass, well defined, in the parietooccipital scalp with no intra-cranial extension. Complete excision of the lesion was carried out. Excision of redundant skin is needed to achieve good aesthetic results. Histopathological examination showed a thin layer of benign stratified squamous epithelium and lamellated keratin debris present in the cyst. There is no sign of malignant transformation. Conclusions. It can be stated that although epidermal cyst is a slow-growing benign tumor, it can cause diagnostic difficulties when located in the scalp area and when there is a possibility that cranial bones and even intracranial structures are affected by the cyst. CT, MRI or ultrasonography are crucial to determine if the cyst contacts intracranial structures. The histopathology examination should be done to detect malignant transformation.